2011
DOI: 10.3989/scimar.03490.21a
|View full text |Cite
|
Sign up to set email alerts
|

<i>Mycale (Aegogropila) magellanica</i> (Porifera: Demospongiae) in the southwestern Atlantic Ocean: endobiotic fauna and new distributional information

Abstract: SUMMARY: The composition of endobionts in the sponge Mycale (Aegogropila) magellanica at the shelf-break, near 100 m depth, in the Argentine Sea was studied. We also provide new information on the distribution of M. (A.) magellanica, extending its northern limit to 38º36.02'S and 55º44.68'W, 91 m in the SW Atlantic Ocean. The main Patagonian scallop fishing grounds are located in the shelf-break frontal area of the Argentine Sea. In this area, M. (A.) magellanica plays an important role in providing habitat fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
1
14
1
Order By: Relevance
“…sponge À1 ) and eight phyla was found in 100 specimens of H. melanadocia. Echinoderms, polychaetes and crustaceans were the dominant groups, which is consistent with other sponge species from different marine environments and regions (Pearse 1950;Duarte & Nalesso 1996;Koukouras et al 1996;Ribeiro et al 2003;Schejter et al 2012).…”
Section: Discussionsupporting
confidence: 88%
“…sponge À1 ) and eight phyla was found in 100 specimens of H. melanadocia. Echinoderms, polychaetes and crustaceans were the dominant groups, which is consistent with other sponge species from different marine environments and regions (Pearse 1950;Duarte & Nalesso 1996;Koukouras et al 1996;Ribeiro et al 2003;Schejter et al 2012).…”
Section: Discussionsupporting
confidence: 88%
“…The role of S. coralliophaga as a biological structure Previous studies on sponge associates have revealed species-rich communities inhabiting sponge canals (e.g., Westinga and Hoetjes 1981;Duarte and Nalesso 1996) and sponges acting as a nursery ground (Schejter et al 2012;Padua et al 2013) providing shelter against strong currents (Peattie and Hoare 1981) and/or predators (Magnino et al 1999a). In contrast to previous studies on sponge infauna, we recorded only a small number of species living inside S. coralliophaga at both MRC and LM.…”
Section: And References Therein)contrasting
confidence: 89%
“…The high values of abundance/biomass in LM coral rubble are attributed to Pseudamussium sulcatum and especially to Asperarca nodulosa whose bathymetric distribution extends from the sublittoral zone to the abyss (Oliver and Allen 1980). Bivalves are often reported as inhabitants of sponge canals (e.g., Ç inar et al 2002;Ribeiro et al 2003;Schejter et al 2012;Padua et al 2013), but the relatively large size of A. nodulosa prevents it from settling in the canals of S. coralliophaga and thus specimens live attached to underlying coral rubble (see also Voultsiadou-Koukoura et al 1987;Gherardi et al 2001;Neves and Omena 2003). In contrast to the LM coral rubble, abundance and biomass of suspension/filter feeders in the MRC coral rubble was low; enhanced water flow conditions, and thus oxygenation/food supply, support the presence of suspension feeders in the LM coral rubble (Lenihan 1999;McQuaid and Mostert 2010;Whitman and Reidenbach 2012).…”
Section: Differences In Community Structure and Possible Driversmentioning
confidence: 99%
“…2 and 3), belonging to the Phyla Arthropoda, Annelida, Mollusca, Nematoda, and Echinodermata with the most abundant classes represented by Crustacea and Polychaeta (Table 1). The taxonomic resolution, to the ordinal rank yielded similar patterns and associated taxa between C. lutea and other sponges belonging to the class Demospongiae, with crustaceans being the most abundant (Pease 1950; Pansini 1970; Rützler 1976; Koukouras et al 1985; Voultsiadou-Koukoura et al 1987; Villamizar and Laughlin 1991; Koukouras et al 1992; Ribeiro et al 2003; Skilleter et al 2005; Abdo 2007; Palpandi et al 2007; Huang et al 2008; Greene 2008; Schejter et al 2012; Kersken et al 2014; and Gerovasileiou et al 2016). However, several other studies reported in Appendix 1 of Schejter et al (2012) found Polychaetes to be the most abundant associated organisms.…”
Section: Discussionmentioning
confidence: 78%
“…Most of the studies regarding marine sponges and their associated fauna have focused on the class Demospongiae; perhaps because 86% of the extant Porifera are Demospongiae (van Soest et al, 2016). Among the most significant reports concerning demosponge-associated fauna were those of Santucci (1922), Pearse (1932, 1950), Fishelson (1966), Long (1968), Pansini (1970), Sube (1970), Labate & D’Addaboo (1974), Rützler (1976), Peattie & Hoare (1981), Koukouras et al (1985), Wendt et al (1985), Voultsiadou-Koukoura et al (1987), Koukouras et al (1992), Klitgaard (1995), Koukouras et al (1996), Duffy (1996), Magnino et al (1999), Ribeiro et al (2003), Skilleter et al (2005), Abdo (2007), Palpandi et al (2007), Huang et al (2008), Greene (2008), Schejter et al (2012), Sivadas et al (2014), and Schönberg et al (2015). Of the mentioned studies regarding the associated organisms of demosponges, the most represented phyla are Arthropoda, Annelida, Mollusca, Nematoda, and Echinodermata and the most abundant classes are Crustacea, Polychaeta, and Ophiuroidea.…”
Section: Introductionmentioning
confidence: 99%